Integrating Unplugged Coding into Elementary Physical Education: An Embodied Computational Thinking Approach - Hendra Puspita (The Indonesian Institute of Science and Technology Research, 2026)
The integration of computational thinking (CT) into primary education has expanded rapidly, yet its application in non-STEM domains remains limited. This study investigates how unplugged coding can be embedded within elementary physical education (PE) through an embodied learning approach. Using a qualitative case study design, data were collected through an in-depth interview with a PE teacher who implemented unplugged coding after completing a four-month professional training program. Findings reveal that CT principles—particularly sequencing and algorithmic thinking—can be effectively translated into movement-based instruction. The teacher operationalized coding as structured movement sequences, supported by visual mapping, collaborative learning, and field-based practice. Students demonstrated increased engagement, improved conceptual understanding of motor sequences, and heightened motivation. The study contributes to interdisciplinary pedagogy by proposing an “embodied computational thinking” model that integrates cognitive and kinesthetic learning. The findings have implications for curriculum innovation, teacher professional development, and equitable access to CT education without reliance on digital technologies.